Operations management in the hospitality industry - Szende, Peter; Dalton, Alec N.; Yoo, Michelle (Myongjee) (Emerald Publishing Limited, 2021)
From restaurants to resorts, the hospitality industry demands strong operations management to delight guests, develop employees, and deliver financial returns. This introductory text provides students with fundamental techniques and tools to analyse and improve operational capabilities of any hospitality organization. This book spans a breadth of topics critical to today's operations leaders. Each topic surveys key theories, frameworks, and industry examples, with additional depth achieved through engaging learning features. Uniquely, the book is set out in standalone chapters that can be digested individually or together; allowing flexibility for instructors and readers seeking to learn specific subject matter. Whether a student preparing for their career, or a professional seeking tools, readers will gain valuable knowledge from operations management in the hospitality industry.
Includes index.
Keywords: Hospitality industry -- Management.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality industry.; elektronické knihy; electronic books